Respiratory syncytial virus infection of airway epithelial cells, in vivo and in vitro, supports pulmonary antibody responses by inducing expression of the B cell differentiation factor BAFF. Issue 1 (21st September 2012) - McNamara, P S; Fonceca, A M; Howarth, D; Correia, J B; Slupsky, J R; Trinick, R E; Al Turaiki, W; Smyth, R L; Flanagan, B F
Abstract : Background: The mechanisms regulating antibody expression within the human lung during airway infection are largely unknown. In this study, our objectives were to determine if infection with respiratory syncytial virus (RSV) upregulates expression of the B cell differentiation factors A proliferation inducing ligand (APRIL) and B cell activating factor of the TNF family (BAFF), if this is a common feature of viral airway infection, and how this is regulated in human airway epithelial cells. Methods: We measured BAFF and APRIL protein expression in bronchoalveolar lavage (BAL) fluid from infants with severe RSV disease, and healthy control children, and in nasopharyngeal aspirates from preschool children with other single respiratory viral infections. We also measured mRNA expression in bronchial brushings from RSV-infected infants, and in RSV-infected paediatric primary airway epithelial cell cultures (pAEC). Beas-2B cell cultures were used to examine mechanisms regulating BAFF expression. Results: BAFF protein and mRNA were elevated (in marked contrast with APRIL) in BAL and bronchial brushings, respectively, from RSV-infected infants. BAFF protein was also found in upper airway secretions from children with human metapneumovirus, H1N1, bocavirus, rhinovirus, RSV and Mycoplasma pneumoniae infection. BAFF mRNA and protein were expressed following in vitro RSV infection of both pAEC and Beas-2B cultures, with mRNA expression peaking 12-h postinfection. BAFF induction was blocked by addition of a neutralising anti-interferon-β antibody or palivizumab. Conclusions: BAFF, produced through an interferon-β-dependant process, is a consistent feature of airway infection, and suggests a role for the airway epithelia in supporting protective antibody and B cell responses in the lung.